Control strategy for an industrial process monitoring robot - Zimber, Fabian; Horváth, Csongor Márk; Thomessen, Trygve; Franke, Jörg (SII 2016 - 2016 IEEE/SICE International Symposium on System Integration, 2017)
The installation of industrial robot systems requires considerable human effort both related to the mechanical and electromechanical setup. However, the task of programming a robot is of particular importance to satisfy given process requirements. Typically, only 20% of the entire programming time is needed to define the path and logics while the remaining 80% is related to process optimization. This causes considerable costs due to the need for human presence. With a remote assistance system and a process monitoring robot, expert assistance could be decoupled from the physical presence. An important challenge is to solve the tracking between the monitoring robot and the robot performing the process. In this paper we propose a controllable sensor system for enhanced process monitoring. The system is decoupled from the process tool and can therefore be controlled independently. It provides the machine operator with adaptive process information and enhances the capabilities to qualify complex processes. We apply the concept to an autonomous sensor robot monitoring an industrial robot system for heavy, multipass TIG welding of voluminous workpieces.
CRIS-Team Scopus Importer:2023-03-07